2022-LBA-592-ESGO Primary prevention of HPV-related diseases from the patients' perspective in Poland – an interim analysis. (27th October 2022) - Trojnarska, Dominika; Jach, Robert
Abstract : Introduction: The aim of this study was to determine the general knowledge about human papillomavirus (HPV) and the attitude towards primary prevention among Polish patients. From November 2021, the bivalent vaccine in Poland is co-financed by the state at 50%. This partial coverage includes all registered indications in persons aged 9 years and older for the prevention of HPV-related diseases. Methods: A questionnaire consisting of 11 questions was given to each patient referred to the dysplasia consultation at Kraków University Hospital from February 2022. The questionnaire consisted of a section on knowledge about HPV infection and patients' attitudes towards HPV vaccination, as well as a demographic assessment of the study group. The patients were also asked about the coverage of costs for the vaccination. Results: By July 2022, 125 completed forms had been received. The overwhelming majority of women participating in the survey were between 30 and 40 years of age from large cities with populations greater than 100, 000 and with higher education. A large majority had heard of HPV (83.2%) and correctly associated it with an increased risk of cancer (69.6%) and abnormal Pap-test results (75.2%). Women know that the infection is sexually transmitted (65.6%) and asymptomatic (46.4%). They are generally willing to have themselves and their children, especially their daughters, vaccinated but only three of the 125 surveyed women had already got the vaccine, and three had their children vaccinated. Only 20.0% knew about the governmental co-financing of the vaccine. Conclusions: The results so far indicate that current campaigns promoting vaccination are insufficient and require action. It can be expected that with increased knowledge of the co-financing more people will be vaccinated.